DESIGN, VALIDATION, AND RELIABILITY OF AN OBSERVATIONAL INSTRUMENT FOR THE DEFENSIVE AND OFFENSIVE TECHNICAL-TACTICAL ACTIONS OF THE GOALKEEPER (Kinesiology, 2020)
The aim of this study was to design and validate an observational instrument to analyse the behaviour of the goalkeeper in defence and attack. The validation and reliability processes were carried out by 12 experts, who were required to fulfill at least two of five selected requirements. Content validity was calculated using Aiken’s V. The Kappa Index was used to analyse reliability. The observational tool was divided into 3 different blocks: offensive actions, defensive actions, and actions taken before the defensive action of the goalkeeper. Only three of the total items achieved low values, with modifications, recording optimal values in accordance with Aiken’s V. Following the first step of the process taken by the experts, the new proposals were evaluated after a pilot test. The reliability test scored optimal values. An observational sheet was developed to manage the quantitative and qualitative assessments of the experts, and this tool was accepted as valid and reliable.